2008
DOI: 10.4314/sjms.v3i2.38528
|View full text |Cite
|
Sign up to set email alerts
|

Quinolones Resistance And R-Plasmids Of Clinical Isolates Of <i>Pseudomonas</i> Species

Abstract: Background: There has been reported incidence in the emergence of Quinolones resistance in clinical isolates in Nigeria and the level in resistance has been on the increase. Objective: To determine the antimicrobial resistance patterns and plasmids profiles of 67 clinical Pseudomonas species from a teaching hospital and diagnostic laboratory in Nigeria. Materials and methods: The Pseudomonas species were identified and confirmed by standard procedures. The antibiotic susceptibility patterns were determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Several previous studies carried out in different settings also support the multi-drug resistance pattern of Pseudomonas spp. 24 26 . The mechanisms of intrinsic resistance of Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies carried out in different settings also support the multi-drug resistance pattern of Pseudomonas spp. 24 26 . The mechanisms of intrinsic resistance of Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of MDR and ESBL E. coli pose antibiotic management problems (Lim et al, 2009). Multiple antibiotic resistances in bacteria and production of ESBL is most commonly associated with the presence of plasmids which contain one or more resistance genes, each coding a single antibiotic resistance phenotype (Paterson et al, 2005;Daini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The types of antibiotics and their frequency of usage in the various patients from whom the specimens were taken may be the cause of the diversity in the resistance pattern of P. vulgaris isolates. However, [21] found that all Proteus isolates were sensitive to ciprofloxacin whereas [22] revealed that the isolates of P. vulgaris were resistant to ciprofloxacin. [23] showed that (80%)…”
Section: Resultsmentioning
confidence: 99%